An investigation of the resistive switching in individual and networks of nickel nanowires - Bell, Alan P. (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
Nickel/nickel oxide core-shell nanowires can be transformed from their native electrically insulating state to a conductive state by the formation of an atomic scale conductive filament bridging the oxide. This resistive switching can be utilised to store information: a conductive state can be thought of as ON or 1, and insulating, an OFF or 0 state. In this thesis we fabricated networks of nickel nanowires and subsequently contacted these networks using a two-step lithography. This contacting was required to enable electrical characterisation of the networks.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin